Uncovering the Dynamics of Multi‐Sector Impacts of Hydrological Extremes: A Methods Overview - Mariana Madruga de Brito; Jan Sodoge; Alexander Fekete; Michael Hagenlocher; Elco Koks; Christian Kuhlicke; Gabriele Messori; Marleen de Ruiter; Pia‐Johanna Schweizer; Philip J. Ward (Earth's Future, 2024)
Abstract Hydrological extremes, such as droughts and floods, can trigger a complex web of compound and cascading impacts (CCI) due to interdependencies between coupled natural and social systems. However, current decision‐making processes typically only consider one impact and disaster event at a time, ignoring causal chains, feedback loops, and conditional dependencies between impacts. Analyses capturing these complex patterns across space and time are thus needed to inform effective adaptation planning. This perspective paper aims to bridge this critical gap by presenting methods for assessing the dynamics of the multi‐sector CCI of hydrological extremes. We discuss existing challenges, good practices, and potential ways forward. Rather than pursuing a single methodological approach, we advocate for methodological pluralism. We see complementary or even convergent roles for analyses based on quantitative (e.g., data‐mining, systems modeling) and qualitative methods (e.g., mental models, qualitative storylines). The data‐driven and knowledge‐driven methods provided here can serve as a useful starting point for understanding the dynamics of both high‐frequency CCI and low‐likelihood but high‐impact CCI. With this perspective, we hope to foster research on CCI to improve the development of adaptation strategies for reducing the risk of hydrological extremes.